ANALISIS PENERAPAN METODE PENYUSUTAN AKTIVA TETAP DAN PENGARUHNYA TERHADAP LABA CV. AL- GAZALI DI KABUPATEN BERAU (ACCOUNTING STUDY PROGRAM, UNIVERSITAS MUHAMMADIYAH BERAU, 2017)
Analysis of Application of Depreciation Method of Fixed Assets to Profit CV. Al-Gazali In the District of Berau. The purpose of this study is to find out how much profit from each method on the CV. Al-Gazali. The data obtained is a breakdown of the budget cost from the year of development that is 2014-2015 which is used as a reference in determining the factors of the method depreciation. With the above purposes, the analytical instrument used in this study are the Method of Depreciation of Fixed Assets, balance sheet and Income Statement. Depreciation Cost of Standard of Fixed Assets as a whole by 2014 According to CV. AlGazali in Berau District is amount Rp. 57.775.000, - with accumulated depreciation of amount Rp. 617.825.000, -. Thus, a budget of that company that is setting in accordance with the current economic situation, Therefore, the sales results can increase production well and direct the workforce in order to perform their duties more effectively and efficiently.